Women in STEM and TVET: A Systematic Review of Participation, Barriers, and Career Development (2022–2026) - Muhammad Akbar; Nurhasan Syah; Muhammad Giatman (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
In the era of digital transformation and the green economy, women's participation in STEM fields as well as Technical and Vocational Education and Training (TVET) is essential to achieving gender equality and meeting labour market needs. Gender differences in STEM education and employment continue to exist in many countries despite various laws intended to boost women's involvement. The purpose of this project is to investigate research trends, participation types, obstacles, and career development tactics for women in STEM and TVET between 2022 and 2026. The PRISMA 2020 guidelines were followed for conducting a Systematic Literature Review (SLR). Using keywords like women, STEM, TVET, gender equality, and career development, articles were located in the ScienceDirect database. The results show that there has been an upsurge in study on women in STEM and TVET, with an emphasis on career development, mentorship, role models, gender hurdles, and women's involvement. Gender stereotypes, discrimination, poor self-efficacy, and restricted access to mentors and professional networks are the most commonly mentioned obstacles. Strengthening mentorship programs, offering female role models, fostering digital capabilities, and enacting more equitable labour and education laws are among suggested tactics. The findings of this study have significance for developing gender-equitable vocational education programs that support women's long-term employment in STEM fields.